A Case Report of Neurocysticercosis at Sanglah Hospital, Denpasar, Bali - A.A Raka Sudewi; Ge Aris Geson; Ivan Elisabeth Purba; Toni Wandra (The Indonesian Journal of Infectious Diseases, 2013)
We reported one neurocysticercosis (NCC) case who visited neurological outpatient clinic of Sanglah hospital, Denpasar, Bali. The patient is a 46-year-old man from Sumba, East Nusa Tenggara Province, and eastern part of Indonesia. The main symptoms of patient was headache and history of epileptic seizures, and spastic monoparesis on left lower limb. Diagnosis and follow up patient was performed clinically including CT scan and serologically. Detection of specific antibodies to Taenia solium in serum was performed by ELISA and immunoblot using native and recombinant antigens.